2015
DOI: 10.1016/j.jvs.2015.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and complications after aortic bifurcated bypass procedures for chronic aortoiliac occlusive disease

Abstract: Aortic bifurcated bypass is a high-risk procedure. Although open surgery has increasingly given way to endovascular repair, 30-day outcomes have remained stable during the past decade. Thus, it is still acceptable to consider an aortic bifurcated bypass whenever endovascular management is not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 15 publications
5
35
1
2
Order By: Relevance
“…Given the relatively high morbidity rates despite the generally excellent patency results following AFB, caution is necessary with high risk patients. 3 AFB patients were relatively young, with a mean age of 59.6 AE 8.5 years, which is consistent with the average age reported in other studies. 13e15 Overall, AFB patients in this series had the least comorbidities and were less likely to have elevated serum creatinine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given the relatively high morbidity rates despite the generally excellent patency results following AFB, caution is necessary with high risk patients. 3 AFB patients were relatively young, with a mean age of 59.6 AE 8.5 years, which is consistent with the average age reported in other studies. 13e15 Overall, AFB patients in this series had the least comorbidities and were less likely to have elevated serum creatinine.…”
Section: Discussionsupporting
confidence: 90%
“…1,2 Such a change in treatment approach may explain the potentially increased complexity of open reconstructions, including aortofemoral bypass (AFB), which are now essentially reserved for more surgically challenging cases. 2,3 This paradigm shift has also affected training programs so that now AFB is hardly performed by the graduating trainees of vascular programs. 1,4,5 Older patients with more advanced comorbidities and diffuse atherosclerosis or a combination of more proximal aneurysmal disease and common/external iliac occlusive disease are still more likely to require open surgical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The durability of the AbF bypass is offset by the low rate of morbidity and mortality of the kissing stent technique, which on the contrary has been questioned in terms of long-term patency and need of reinterventions. 19,[21][22][23] A recent review showed that AbF bypass grafting had a higher mortality than the kissing stent technique; that study highlighted the impact of the higher incidences of coronary and respiratory diseases in patients undergoing open repair. 19 This was surprising, probably because of the fact that anatomically suitable lesions were preferentially treated with the kissing stent technique regardless of the patients' comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to make comparative conclusions regarding major complications after ABF due to the widely variable definitions used in the literature. 5,7,15,16,21 Our definition was a composite variable of 13 different outcomes and occurred in 35.9% of our cohort. This most commonly took the form of unplanned 30-day readmission, unplanned return to the OR, and respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5e9 The desire to avoid these complications, especially in older frail and comorbid patients, led to a shift in treatment paradigms favoring endovascular techniques for AIOD demonstrated by a dramatic decrease in ABF volume nationwide. 5,10 Although consensus guidelines have recommended the use of endovascular therapy in less-complex and extensive disease (Trans-Atlantic Inter-Society Consensus [TASC] A and B lesions), studies have shown success of endovascular techniques in more advanced anatomy (TASC C and D lesions). 6,11e13 This further shift has resulted in ABF being reserved for patients with long-segment, multilevel, highly calcified AIOD or failed endovascular therapy translating to increased operative complexity in the modern era.…”
Section: Introductionmentioning
confidence: 99%